THE PRINCIPLE OF MUTUAL RECOGNITION IN ASSOCIATION OF SOUTHEAST ASIAN NATIONS FREE TRADE - Nasution, Siti Nurahmi; Adwani, Adwani; Sutiarnoto, Sutiarnoto; Leviza, Jelly (Ultimate Journal of Legal Studies, 2023)
This essay intends to examine the ASEAN Free Trade Agreement's implementation and the ASEAN Free Trade Agreement's recognition concept. This paper's research was conducted using normative legal research techniques. Secondary sources were used as the primary source of information for this investigation. Documents and scientific publications from the library are examples of secondary materials. Laws and regulations, agreements, legal theories, and future scientific works are only a few examples of the legal papers that have been used as literary resources. The concept of recognition in ASEAN free trade is the subject of this normative study, which will be explained analytically as a whole object methodically in light of the facts gathered.